Study on interlocking concrete block pavement made with sugarcane bagass - Siti Irniza Azimah Hamzah (School of Environmental Engineering, University Malaysia Perlis, 2012)
The recycling of solid waste in civil engineering applications has undergone considerable handling cost of brick production. Many types of aggregates available that are closed a lightweight, and theory properties of structural lightweight aggregates concrete are dependent on the type of lightweight aggregate utilized in the concrete. The development over a very long time. The use of solid waste fiber reduces the dead weight and mater. Purposed undertake the project namely Study On Interlocking Concrete Paving Block (ICBP) Made With Sugarcane Bagasse. Get reading value compression strength supply mixture in the interlocking paving block which have been produced by using 1:3 (cement : sand). It afford match present strength of interlocking paving block or no. right some procedure must abide to generate sugarcane bagasse mixture. By using 10 %, 15% and 20% replace sand in the interlocking paving block. 42 specimens produced for air curing 7 and 28 days include water absorption specimens. The results of compression test, the optimum strength 2.475 MPa. Results of water absorption 14.58% to 21.16%, which high water absorption correlation to strengh ICBP. For density ICBP about 1525 kg/m3 to 1775 kg/m3. For this thesis interlocking concrete paving block suitable for light structure. Interlocking concrete paving block place such as pedestrian roofed area, which the area did not have heavy structure.